The Turning Tide : How Vulnerable are Asian Corporates? - Jiang, Bo (IMF Working Papers; Working Paper ;, 2019)
Using a new firm-level dataset with comprehensive information on Asian firms' FX liabilities, we show that Asia's nonfinancial corporate sector is vulnerable to a tightening of global financial conditions. Higher global interest rates and exchange rate depreciation increase the probability of default of Asian firms. A 30 percent currency depreciation is associated with a two-notch downgrade in the corporate credit rating (e.g., from A to BBB+), resulting in 7 percent of Asian firms falling into bankruptcy. But the impact is nonlinear-as the firms' FX liability increases, the balance sheet channel of exchange rate offsets, then dominates, the competitiveness channel. The balance sheet channel offsets the competitiveness channel when the share of U.S. dollar debt is between 10 and 20 percent. We also find that currency depreciation increases firm-level investment on average, but for firms with the share of FX liabilities above 20 percent, investment contracts with depreciation.